2009
DOI: 10.1093/ndt/gfp598
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammation and protein-energy wasting with endothelial dysfunction in peritoneal dialysis patients

Abstract: Background. Cardiovascular disease is the main cause of mortality in end-stage renal disease (ESRD) patients. Recent studies have indicated that non-traditional risk factors such as endothelial dysfunction (ED), chronic inflammation and protein-energy wasting (PEW) may contribute significantly to the increased cardiovascular mortality among dialysis patients. To further ascertain this association, we carried out a cross-sectional assessment of nutritional status, inflammatory markers and endothelial dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
(40 reference statements)
1
31
1
Order By: Relevance
“…Glucose and glucose degradation products in the PD solutions can increase CRP levels of PD patients (35,36). CRP is known to positively correlate with cardiovascular events and mortality in PD patients (3,7,(14)(15)(16)(17). In our study, although the CRP polymorphism did not correlate with survival for the entire cohort, we found that the polymorphism had a significant interaction with plasma cholesterol levels.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Glucose and glucose degradation products in the PD solutions can increase CRP levels of PD patients (35,36). CRP is known to positively correlate with cardiovascular events and mortality in PD patients (3,7,(14)(15)(16)(17). In our study, although the CRP polymorphism did not correlate with survival for the entire cohort, we found that the polymorphism had a significant interaction with plasma cholesterol levels.…”
Section: Discussioncontrasting
confidence: 59%
“…Most patients undergoing PD enjoy excellent survival rates, as well as a good quality of life during treatment (2). Nonetheless, PD imposes oxidative stress, which may lead to systemic inflammation and aggravate atherosclerotic lesions (3)(4)(5)(6)(7). Glucose, glucose degradation products, and advanced glycation end products are probably the major causative factors of inflammation in PD patients (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous in vitro and animal studies showed superior biocompatibility of multichamber PD solutions (1)(2)(3)(4)(5). Recent randomized controlled trials suggest improved preservation of residual renal function (6,7) and ultrafiltration capacity (8) and lowering of systemic concentrations of advanced glycation end products (9,10), which contribute to accelerated vasculopathy and amyloidosis. Registry findings suggest an improved patient survival with low-GDP fluids (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Most PD patients can enjoy an impressive survival rate and an excellent quality of life during the treatment [2]. However, PD is known to cause inflammation and oxidative stress, which may aggravate atherosclerotic lesions [3,4,5,6,7]. In fact, cardiovascular disease is the major cause of morbidity and mortality in PD patients [8,9].…”
Section: Introductionmentioning
confidence: 99%